Multilayer ferrite inductors for the use at high temperatures. Issue 2 (12th May 2020) - Bartsch, Heike; Thiele, Sebastian; Mueller, Jens; Schabbel, Dirk; Capraro, Beate; Reimann, Timmy; Grund, Steffen; Töpfer, Jörg
Abstract : Purpose: This paper aims to investigate the usability of the nickel copper zinc ferrite with the composition Ni0.4 Cu0.2 Zn0.4 Fe1.98 O3.99 for the realization of high-temperature multilayer coils as discrete components and integrated, buried function units in low temperature cofired ceramics (LTCC). Design/methodology/approach: LTCC tapes were cast and test components were produced as multilayer coils and as embedded coils in a dielectric tape. Different metallization pastes are compared. The properties of the components were measured at room temperature and higher temperature up to 250°C. The results are compared with simulation data. Findings: The silver palladium paste revealed the highest inductance values within the study. The measured characteristics over a frequency range from 1 MHz to 100 MHz agree qualitatively with the measurements obtained from toroidal test samples. The inductance increases with increasing temperature and this influence is lower than 10%. The characteristic of embedded coils is comparable with this of multilayer components. The effective permeability of the ferrite material reaches values around 130. Research limitations/implications: The research results based on a limited number of experiments; therefore, the results should be verified considering higher sample sizes. Practical implications: The results encourage the further investigation of the material Ni0.4 Cu0.2 Zn0.4 Fe1.98 O3.99 for the use as high-temperature ferrite for the design of multilayer coils with an operation frequency in the range of 5-10 MHz and operation temperatures up to 250°C. Originality/value: It is demonstrated for the first time, that the material Ni0.4 Cu0.2 Zn0.4 Fe1.98 O3.99 is suitable for the realization of high-temperature multilayer coils and embedded coils in LTCC circuit carriers with high performance.